In-Silico Profiling of New Mefenamic Acid Derivatives as HDAC 8 Inhibitors - Ali, Zainab; Hamzah, Mohammed J; Alwash, Ameer H. (Journal of Pharmacology and Drug Development, 2026)
Vital cellular processes such as, proliferation and tumor progression were reported to be centrally controlled by histone deacetylase (HDAC) enzymes which make them an interesting therapeutic target. Recently, a new paradigm has attracted researches to combine nonsteroidal anti-inflammatory drugs (NSAIDs) with para-aminobenzoic acid (PABA) and a zinc binding group (ZBG), presenting a synergistic impact on HDAC activity and inflammatory process. In the current study, a novel series of hybrid compounds (A1-6) were designed and evaluated for their HDAC binding affinity by molecular docking technique along with conducting an in-silico ADME (absorption, distribution, metabolism, and elimination) profiling to assess their pharmacokinetic characteristics. Compound A6 displayed the highest binding energy score (-9.539 kcal/mol) with the active site of HDAC 8 enzyme compared with the reference ligand, SAHA (-4.606 kcal/mol). Its worth mentioning that compound A6 has comparable coordination to the catalytic zinc ion with SAHA along with engaging additional hydrophobic and aromatic interaction within the active site of HDAC 8 enzyme. ADME analysis predicated high gastrointestinal absorption for A2, A5, and A6, which also comply with Lipinski’s rule, indicating good oral bioavailability. Conversely, A1, A3, and A4 showed moderate absorption, suitable for parenteral or localized/colon-targeted delivery, potentially advantageous for colon cancer treatment. These results highlight these hybrids’ potential as HDAC inhibitors and support further synthesis and biological testing.